2019
DOI: 10.1039/c9cc00271e
|View full text |Cite
|
Sign up to set email alerts
|

Underwater manipulation of oil droplets and bubbles on superhydrophobic surfaces via switchable adhesion

Abstract: UV light-responsive reversible switching of oil droplet and bubble adhesion underwater is realized to manipulate oil droplet or bubble motion and transportation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Among different separation technologies that are applicable to industrial processes as well as our daily life 14,15 , membrane-shaped materials, such as mesh 1622 , fabric 2326 , and membrane materials 2729 , have been gained widespread interest due to higher separation efficiency and probable use in large scale manufacturing 3034 . Since surface wettability of these textured membranes can dramatically affect water or oil droplet adhesion between substrates, and hence affect the oil/water separation process 3539 , designing and preparing wettability switchable membranes would be a convincing way to enable the separation process on demand 4045 .…”
Section: Introductionmentioning
confidence: 99%
“…Among different separation technologies that are applicable to industrial processes as well as our daily life 14,15 , membrane-shaped materials, such as mesh 1622 , fabric 2326 , and membrane materials 2729 , have been gained widespread interest due to higher separation efficiency and probable use in large scale manufacturing 3034 . Since surface wettability of these textured membranes can dramatically affect water or oil droplet adhesion between substrates, and hence affect the oil/water separation process 3539 , designing and preparing wettability switchable membranes would be a convincing way to enable the separation process on demand 4045 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the smart surface with switchable wettability can not only control the adhesion of droplets but also the gas and underwater oil, further helping to provide new opportunities for the development of smart switchable surfaces. Guo's team produced a smart superwetting surface with the properties of manipulation oil droplets and bubbles underwater via switchable adhesion upon ultraviolet response [176] . Liu et al reported a novel oil-triggered surface by switching wettability property between lotus-leaf and nepenthes, which was used in various droplet manipulation modes with real-time property [121] .…”
Section: Smart Soft Roboticmentioning
confidence: 99%
“…Copper T-shaped grooves 152.5˚ [197] Copper foil Microscale craters and nanoparticles 171˚ [198] Titanium alloy Randomly-distributed hemispherical features - [199] Electrochemical etching CA = contact angle, SA = sliding angle. Water CA is used to quantitatively compare among superhydrophobic surfaces.…”
Section: Aluminum Alloymentioning
confidence: 99%